The Effects of in-Home Respite Care on the Burden of Caregivers in Taiwan. (May 2022) - Liao, Yi-Han; Ku, Li-Jung Elizabeth; Liu, Li-Fan; Li, Chung-Yi
The utilization rate of respite care in Taiwan is low, and past studies that evaluated the effects of in-home respite care on caregiver burden are few. This two-wave panel study used Taiwan's long-term care plan 1.0 database and included 2342 care recipient–caregiver dyads who used home services to examine the impact of in-home respite care on caregiver burden. Propensity score matching was used to select 323 in-home respite service users matched with 646 nonusers as control groups (1:2 matching). The mixed effect model was applied to estimate the effects of receiving in-home respite care on caregiver burden. Results showed that compared with those of nonusers, caregiver burden scores of service users decreased significantly after receiving in-home respite care for more than 14 days (adjusted B = −0.14, SE = 0.05). The government should prioritize increasing the number of days of in-home respite care for those in need to reduce the caregiver burden.